Core Values of Family Physicians and General Practitioners in the African Context - Lawson, Henry J. O.; Nortey, David N. N. (Frontiers in Medicine, 2021)
Abstract Introduction: Family Medicine is a growing specialty in the medical world. While it is expected that the specialty should have its own unique and established core values and tasks, the breath of the practice in several countries of the world has made this a daunting task. Core values and Tasks have far reaching effects on professions. They guide development of curricula, methods of instruction, standards of performance and even the culture of the profession. We aimed to explore the core value system of Family Physicians and General Practitioners practicing in Africa. Methods: Using the Delphi technique, a purposive selection of African Family Medicine practitioners in academia, public service, private practice and clinical training across Central, East, North, South and West Africa was conducted. Participants were asked to select five core values from an alphabetically collated list of 29 core values in an online survey. The five most selected core values were collated and sent out in the second round to the participants to rank in order of importance. Results: Practitioners from nine African countries in three out of the five United Nations subregions of Africa completed the study. The first round of the study saw participation of a team of nineteen experts who selected the following five core values – Comprehensive care, Continuity of Care, Collaborative Care, Patient centered care and Life-long learning. In the second round, a smaller number of experts selected Comprehensive Care as the most important core value for Family Physicians and General Practitioners in the African Context. Discussion/Conclusion: The core value of utmost interest and of highest concern was Comprehensive care. Most African practitioners work in environments where there is scarcity of facilities for higher care hence several diagnoses which may require referral have to be managed initially at the first facility where the patient reports to before referral processes can be initiated. These core values should also guide development of curricula, training methods and a benchmark for standards of practice for the specialty in Africa.